Systematic Literature Review: Peran Kepemimpinan Transformasional Dan Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan Outsourcing - Alfani Alifia Ardila; Mohammad Khusnu Milad (Jurnal Ilmiah Ekonomika & Sains, 2025)
Improving the performance of outsourcing employees has become a strategic challenge for modern organizations that rely on workforce flexibility and efficiency. Outsourced workers often face limited job security, restricted career development, and low psychological attachment to their host organizations. This study aims to systematically analyze the role of transformational leadership and organizational culture in enhancing the performance of outsourcing employees. The research employed a Systematic Literature Review (SLR) method by examining twenty peer-reviewed journal articles published between 2015 and 2025. The review process followed the PRISMA guidelines, including identification, screening, eligibility, and synthesis stages to ensure analytical transparency and validity. The findings reveal that transformational leadership and organizational culture have a significant and positive influence both partially and simultaneously on outsourcing employee performance. Transformational leadership enhances motivation, commitment, and individual responsibility through inspirational communication and moral integrity, while organizational culture acts as a collective value system that strengthens belongingness and social integration. The interaction between the two creates a synergistic effect that improves productivity, loyalty, and job satisfaction among outsourced employees. This review concludes that the success of outsourcing systems depends not only on contractual and supervisory mechanisms but also on the consistent implementation of transformational leadership aligned with an inclusive and adaptive organizational culture. Keywords: transformational leadership, organizational culture, employee performance, outsourcing employees, systematic literature review.